2003
DOI: 10.1159/000072251
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Evidence of nNOS and Changes after Intraglandular Application of Botulinum Toxin A in Cephalic Salivary Glands of Adult Rats

Abstract: The purpose of our study was to investigate the possible influence of local injections of botulinum toxin A on the activity of neuronal nitric oxide synthase (nNOS) in cephalic salivary glands of adult rats. The role of nitric oxide (NO) as a possible neuromodulator of vascular regulation and in particular regulation of secretion in the upper respiratory and aerodigestive tract is discussed. We present immunohistochemical evidence of nNOS in the salivary glands of female adult Wistar rats, both in native (untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Currently, experimental studies of the action of botulinum toxin in salivary glands follow a pattern, in rats, and the majority refers to immunohistochemical studies. Immunohistochemical investigations were made mainly for the enzyme acetylcholinesterase (AChE) and neuronal nitric oxide synthase (nNOS) in submandibular and/or parotid glands of female rats, such as publications of Ellies et al (1999Ellies et al ( , 2000Ellies et al ( , 2003Ellies et al ( , 2006a and Ellies (2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, experimental studies of the action of botulinum toxin in salivary glands follow a pattern, in rats, and the majority refers to immunohistochemical studies. Immunohistochemical investigations were made mainly for the enzyme acetylcholinesterase (AChE) and neuronal nitric oxide synthase (nNOS) in submandibular and/or parotid glands of female rats, such as publications of Ellies et al (1999Ellies et al ( , 2000Ellies et al ( , 2003Ellies et al ( , 2006a and Ellies (2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, besides acetylcholine transmitters, other neurotransmitters, such as NO neuromodulator may also be involved in regulating the function of the salivary gland (Ellies et al, , 2006a. Ellies et al (1999Ellies et al ( , 2000Ellies et al ( , 2003Ellies et al ( , 2006a and Ellies (2003), tested the immunoreactivity for acetylcholinesterase and neuronal nitric oxide synthase in parotid and submandibular glands of female rats and demonstrated weak immunoreactivity for these enzymes in the groups treated with botulinum toxin, becoming proportional with the increase of the time exposure to the toxin. According to histological studies in submandibular glands of female rats made by Ellies et al (1999), there is no clear difference of serous acini of glands injected with the toxin and saline in their histometric measurements, although both had a slightly higher nuclear counting than in the acini control group.…”
Section: Discussionmentioning
confidence: 99%
“…Whether there is, in general in analogy to the sweat gland, 23 a potentially longer effectiveness of botulinum toxin at the neuroglandular as opposed to the neuromuscular junction is open to discussion 24 . A possible explanation for the variability might be offered by the decrease in neuronal nitric oxide synthetase (nNOS), which synthesizes the neuromodulator nitric oxide (NO), at the salivary gland cell after application of botulinum toxin type A as observed in animal experiments 25 . The still unanswered question of the duration of botulinum toxin effect on the salivary gland came closer to being answered in our study because there were, in most cases, indications that the effect lasted 3 to 4 months, as shown by the self‐assessment of the patients, by the interval since the preceding injection, and by biochemical parameters (decrease in salivary flow rate and electrolyte secretion, which was demonstrated by thiocyanate).…”
Section: Discussionmentioning
confidence: 99%
“…Because salivary glands are stimulated by acetylcholine like eccrine sweat glands, the use of BTX seems worthwhile. On the other hand, animal studies demonstrated another pathway of action, i.e., the decrease in neuronal nitric oxide system of glands 33 . Using 140 U of Dysport with 100 U injected directly into the gland, the sialorrhea disappeared for 11 months in a 58‐year‐old woman 34 .…”
Section: Btx‐a In Salivary Fistulesmentioning
confidence: 99%
“…On the other hand, animal studies demonstrated another pathway of action, i.e., the decrease in neuronal nitric oxide system of glands. 33 Using 140 U of Dysport with 100 U injected directly into the gland, the sialorrhea disappeared for 11 months in a 58-year-old woman. 34 Two other cases were reported recently involving females who were treated with intraparenchymal injections of either 450 U Dysport or 650 U Dysport, respectively.…”
Section: Btx-a In Salivary Fistulesmentioning
confidence: 99%